Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1590/1983-21252018v31n222rc
|View full text |Cite
|
Sign up to set email alerts
|

Use of S-Index as a Structural Quality Indicator for Compacted Latosols Cultivated With Maize

Abstract: -One way to prevent soil degradation is to monitor its structural quality through physical attributes and indicators. Thus, the objective of this work was to identify parameters that can be used together with the S-index to assess the soil structural quality of Latosols-Distrophic Red Latosol (DRL) and Eutroferric Red Latosol (ERL)-cultivated with maize after traffic-induced compaction by agricultural machinery. The experiment was conducted in a randomized block design in split-plots, with five treatments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Conceptually, this index represents the slope of the line tangent to the inflection point of the SWRC. Several studies, such as Dexter (2004 a, b, c), Assis Júnior et al (2016), Magalhães et al (2018), Rossetti & Centurion (2018), have confirmed the accuracy of the S index using the soil compaction state, which is correlated with the microstructural porosity, bulk density, and soil organic matter content.…”
Section: Introductionmentioning
confidence: 90%
“…Conceptually, this index represents the slope of the line tangent to the inflection point of the SWRC. Several studies, such as Dexter (2004 a, b, c), Assis Júnior et al (2016), Magalhães et al (2018), Rossetti & Centurion (2018), have confirmed the accuracy of the S index using the soil compaction state, which is correlated with the microstructural porosity, bulk density, and soil organic matter content.…”
Section: Introductionmentioning
confidence: 90%
“…For soils of southwest China, Xu et al [16] suggest that the S index has the potential in indicating land management in the catchment scale. S index was used to assess the structural quality of Latosols cultivated with maize [17] and of soils in the Cerrado cultivated with coffee [18].…”
Section: Introductionmentioning
confidence: 99%
“…Este parâmetro (S) é expresso pela porosidade estrutural do solo, ou seja, é resultante da ação de microfendas, trincas, bioporos e poros macroestruturais que são formados devido ao uso e manejo do solo para as culturas. Salienta-se que quanto maior for esse índice (S), melhor será a distribuição de poros do solo por tamanho (ROSSETTI & CENTURION, 2018). De acordo com a distribuição dos diferentes tamanhos de poros, pode-se entender o comportamento físico-hídrico do solo e prever possíveis restrições ao fluxo de água (RIBEIRO et al, 2007).…”
Section: Introductionunclassified